Andean evolution at the Guañacos and Chos Malal fold and thrust belts (36°30′-37°s) - Folguera Telichevsky, Andres (2007)
The Andes between 36°30′ and 37°S represent a Cretaceous fold and thrust belt strongly reactivated in the late Miocene. Most of the features that absorbed Neogene shortening were already uplifted in the late Cretaceous, as revealed by field mapping and confirmed by previous fission track analysis. This Andean section is formed by two sectors: a western-inner sector generated by the closure of the upper Oligocene-lower Miocene intra-arc Cura Mallín basin between the middle and late Miocene (Guañacos fold and thrust belt), and an eastern-outer sector, where late Triassic-early Jurassic extensional depocenters were exhumed in two discrete phases of contraction, in the latest early Cretaceous and late Miocene to the Present, respectively (Chos Malal fold and thrust belt). Late Miocene deformation has not homogeneously reactivated Cretaceous compressive structures, being minimal south of 37°30′S through the eastern-outer sector (southern continuation of the Chos Malal fold and thrust belt). The reason for such an inhomogeneous deformational evolution seems to be related to the development of a late Miocene shallow subduction regime between 34°30′ and 37°45′S, as it was proposed in previous studies. This shallow subduction zone is evidenced by the eastward expansion of the arc that was accompanied by the eastern displacement of the orogenic front at these latitudes. As a result, the Cretaceous fold and thrust belt were strongly reactivated north of 37°30′S producing the major topographic break along the Southern Central Andes.